2019
DOI: 10.5173/ceju.2019.1909
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of candiduria and Candida urinary tract infections in inpatients and outpatients: results from a 10-year retrospective survey

Abstract: Introduction The presence of Candida species in urine (candiduria) is a common clinical finding, which may frequently represent colonization or contamination of specimens, however, they may be etiological agents in urinary tract infections (UTIs) or be indicators of underlying pathology in the genitourinary system or disseminated candidaemia. C. albicans is the most frequently isolated species of the genus, however, an increase in the occurrence of non-albicans Candida species (NACS) has been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 25 publications
0
27
1
14
Order By: Relevance
“…Usually, candiduria is typically asymptomatic and rare in healthy patients, but it is more common in hospitalized patients and especially those in intensive care units (ICU). 1,2 As our previous study indicated, the candiduria incidence rate is as high as 1.61% in hospitalized patients and 22.89% in ICU patients. 3 Diabetes, urinary catheter, female gender, antibiotics, major abdominal surgery and ICU admission are considered as the important risk factors for candiduria.…”
Section: Introductionmentioning
confidence: 93%
“…Usually, candiduria is typically asymptomatic and rare in healthy patients, but it is more common in hospitalized patients and especially those in intensive care units (ICU). 1,2 As our previous study indicated, the candiduria incidence rate is as high as 1.61% in hospitalized patients and 22.89% in ICU patients. 3 Diabetes, urinary catheter, female gender, antibiotics, major abdominal surgery and ICU admission are considered as the important risk factors for candiduria.…”
Section: Introductionmentioning
confidence: 93%
“…Усиление колонизации мочевых путей грибами происходит при наличии мочевого дренажа, конкремента в мочевых путях и после антибактериальной терапии [4,10,12,16,35]. Однако влияние антибактериальной терапии как единственного фактора риска усиления колонизации грибами Candida у женщин с неосложненной ИМП не подтвердилось в исследовании R.M.…”
Section: факторы риска кандидоза мочевыводящих путейunclassified
“…Пребывание больного в отделении реанимации и интенсивной терапии является независимым фактором риска развития мочевой инфекции, вызванной Candida spp. [4,16,35]. По данным W. Hu et al, у пациентов в возрасте старше 65 лет с кандидурией повышенный индекс коморбидности Чарлсона, снижение уровня преальбумина и повышение уровня С-реактивного белка должны рассматриваться как дополнительные факторы риска повышенной летальности [16].…”
Section: факторы риска кандидоза мочевыводящих путейunclassified
See 1 more Smart Citation
“…It is possible to clinically group patients whose urine presents Candida species: Patients with asymptomatic candiduria (previously healthy, outpatients), patients with asymptomatic candiduria (predisposed inpatients), patients with symptomatic candiduria (UTI), and clinically unstable patients with candiduria [9,10]. Once the presence of Candida in the urine is confirmed, careful clinical evaluation should be performed to detect symptoms or suggestive signs of other conditions, such as diabetes mellitus, genitourinary structural abnormalities, decreased renal function, and metabolic syndromes [9][10][11]. For patients with persistent candiduria, treating certain clinical conditions or removing risk factors is usually sufficient to eliminate the presence of Candida in the urine and no antifungal treatment is required [9].…”
Section: Fungal Urinary Tract Infectionmentioning
confidence: 99%